2022
DOI: 10.1038/s41380-022-01755-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of FKBP51 induces stress resilience and alters hippocampal neurogenesis

Abstract: Stress-related psychiatric disorders such as depression are among the leading causes of morbidity and mortality. Considering that many individuals fail to respond to currently available antidepressant drugs, there is a need for antidepressants with novel mechanisms. Polymorphisms in the gene encoding FK506-binding protein 51 (FKBP51), a co-chaperone of the glucocorticoid receptor, have been linked to susceptibility to stress-related psychiatric disorders. Whether this protein can be targeted for their treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 72 publications
3
15
0
Order By: Relevance
“…76, 77 Codagnone et al showed that in primary hippocampal cultures derived from C57BL/6 mice, SAFit2 could increase neurite length, neuronal ramification, and complexity; in rat hippocampal neuronal progenitor cells (NPCs) SAFit2 promoted neurogenesis, neurite outgrowth, and morphological maturation. 74 These results are in line with and further corroborate previous findings reported by Gaali et al, where incubation of human neuroblastoma cells (SH-SY5Y) and mouse neuroblastoma cells (N2a) with SAFit1 showed neurotrophic effects. 3 Overall, these initial studies confirmed the potential of selective FKBP51 inhibitors in the treatment of stress-related psychiatric disorders, even though the current PK properties of SAFit2 are not optimal.…”
Section: Proof Of Concept: Pharmacological Modulation Of Fkbp51 With ...supporting
confidence: 92%
See 4 more Smart Citations
“…76, 77 Codagnone et al showed that in primary hippocampal cultures derived from C57BL/6 mice, SAFit2 could increase neurite length, neuronal ramification, and complexity; in rat hippocampal neuronal progenitor cells (NPCs) SAFit2 promoted neurogenesis, neurite outgrowth, and morphological maturation. 74 These results are in line with and further corroborate previous findings reported by Gaali et al, where incubation of human neuroblastoma cells (SH-SY5Y) and mouse neuroblastoma cells (N2a) with SAFit1 showed neurotrophic effects. 3 Overall, these initial studies confirmed the potential of selective FKBP51 inhibitors in the treatment of stress-related psychiatric disorders, even though the current PK properties of SAFit2 are not optimal.…”
Section: Proof Of Concept: Pharmacological Modulation Of Fkbp51 With ...supporting
confidence: 92%
“…There is mounting evidence that hippocampal neurogenesis is likely to play a protecting role against stress-related diseases as a mechanism of resilience. , Codagnone et al showed that in primary hippocampal cultures derived from C57BL/6 mice, SAFit2 could increase neurite length, neuronal ramification, and complexity; in rat hippocampal neuronal progenitor cells (NPCs) SAFit2 promoted neurogenesis, neurite outgrowth, and morphological maturation . These results are in line with and further corroborate previous findings reported by Gaali et al, where incubation of human neuroblastoma cells (SH-SY5Y) and mouse neuroblastoma cells (N2a) with SAFit1 showed neurotrophic effects …”
Section: Proof Of Concept: Pharmacological Modulation Of Fkbp51 With ...supporting
confidence: 82%
See 3 more Smart Citations